Sovereignty, emergency, legality - Sarat, Austin (New York : Cambridge University Press, 2010)
"It is widely recognized that times of national emergency put legality to its greatest test. In such times we rely on sovereign power to rescue us, to hold the danger at bay. Yet that power can and often does threaten the values of legality itself. Sovereignty, Emergency, Legality examines law's complex relationship to sovereign power and emergency conditions. It puts today's responses to emergency in historical and institutional context, reminding readers of the continuities and discontinuities in the ways emergencies are framed and understood at different times and in different situations. And, in all this, it suggests the need to be less abstract in the way we discuss sovereignty, emergency, and legality. This book concentrates on officials and the choices they make in defining, anticipating, and responding to conditions of emergency as well as the impact of their choices on embodied subjects, whether citizen or stranger"--Provided by publisher.
The 'organic law' of 'ex parte milligan' / David Dyzenhaus -- Comment on Chapter 1 : 'the 'organic law' of 'ex parte milligan / Tony A. Freyer -- Emergency, legality, sovereignty : Birmingham, 1963 / Patrick O. Gudridge -- Comment on Chapter 2 : "Order" in the court / Paul Horwitz -- The banality of emergency : on the time and space of 'political necessity' / Leonard C. Feldman -- Comment on Chapter 3 : Emergencies, body parts and price gouging / J. Shahar Dillbary -- The racial sovereign / Sumi Cho and Gil Gott -- Comment on Chapter 4 : Toward a nonracial sovereign / Debra Lyn Bassett -- Should constitutional democracies redefine emergencies and the legal regimes suitable for them? / Michel Rosenfeld -- Comment on Chapter 5 / James Leonard.
Includes bibliographical references and index.
Keywords: Milligan, Lambdin P; Sovereignty; War and emergency legislation; Rule of law; Constitutional law; Democracy